Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1155/2012/875419
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Antibiotic Susceptibility Pattern ofSalmonella typhiamong Patients Attending a Military Hospital in Minna, Nigeria

Abstract: The threat to human health posed by antibiotic-resistant bacterial pathogens is of growing concern to medical practice. This study investigated the antibiotic sensitivity pattern of Salmonella typhi isolated from blood specimen. One hundred blood samples were collected from suspected typhoid fever patients in 31 Artillery Brigade Medical Centre, Minna, and were analyzed for S. typhi while antibiotic sensitivity testing was done Kirby-Bauer method. Sixty (60.0%) samples out of the total 100 were positive for ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 6 publications
7
27
0
Order By: Relevance
“…These measures cannot be undertaken unless the status of the disease is elucidated. Since infection by Salmonella is reported to be endemic in Nigeria [17], analysis of Salmonella strains and genetic diversity is important for epidemiology of the infection.…”
Section: Introductionmentioning
confidence: 99%
“…These measures cannot be undertaken unless the status of the disease is elucidated. Since infection by Salmonella is reported to be endemic in Nigeria [17], analysis of Salmonella strains and genetic diversity is important for epidemiology of the infection.…”
Section: Introductionmentioning
confidence: 99%
“…Kagambega et al [4] reported Salmonella data in cattle from Burkina Faso, and Adabara et al [5] from hospital cases in Nigeria. Salmonella reports are available in Ethiopia on the prevalence of Salmonella in different food animals, such as cattle, sheep, goats and pigs [1,2,[6][7][8], camels [9], chickens [10] at abattoirs, from animal products at supermarkets [1,2,11], and from human cases [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical Studies in Minna (Nigeria) also revealed a high prevalence of typhoid fever (44.4%) among children within the age group 1-10 years which is also similar with an earlier report of 43.9% prevalence rate in Cebu City, India. It is argued that children are the most vulnerable group, particularly in environments where inadequate water supply and poor environmental hygiene exists combined with a high level of ignorance (Adabara et al, 2012).…”
Section: Epidemiologymentioning
confidence: 99%